(untitled) (EduVision: Journal of Innovations in Pedagogy and Educational Advancements, 2025)
This article analyzes the advantages of using artificial intelligence (AI) technologies in English lessons. The rapid development of the digital educational environment requires innovative approaches to teaching foreign languages. Interactive applications based on artificial intelligence, virtual assistants, automatic translation systems, online testing platforms and adaptive curricula are effective tools for developing students’ linguistic competencies. AI technologies help to organize the educational process in a person-oriented manner, provide an individual approach, encourage students’ independent learning, develop pronunciation, grammar and vocabulary. Also, artificial intelligence tools allow teachers to save time, increase lesson efficiency and improve the assessment system. The study highlights the methodological possibilities and practical advantages of using SI technologies in English language teaching.